2008
DOI: 10.1507/endocrj.k07-073
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of Periostin/OSF-2 Gene in Rat Uterus and Human Endometrium

Abstract: Abstract. Periostin/OSF2 is a ligand for αvβ3 and αvβ5 integrins and activates the Akt/PKB pathway. Recent reports of periostin/OSF2 gene disrupted mice indicate that periostin/OSF-2 plays an important role in implantation. Quantitative RT-PCR revealed that the expression of periostin/OSF-2 mRNA in rat uteri was reduced to approximately 10% at 12 h after 17β-estradiol (E2) injection, but was not changed after progesterone (P) injection. RT-PCR revealed the expression of periostin/OSF-2 in human endometrium, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Due to the critical role of POSTN in metastatic processes, it is very likely that this protein may influence some crucial steps in the implantation process and in the early phases of pregnancy development. Recent reports on null POSTN mice, indicate that POSTN, plays an important role in implantation (59,60). We suggest that POSTN might be involved in regulating the cross-talk between embryonic migrating cells and the endometrium modifying the microenvironment of the target site so as to form a "receptive niche" and allowing blastocyst migration, attachment and invasion.…”
Section: Human Embryo Implantation Shares Many Biological Characterismentioning
confidence: 76%
See 3 more Smart Citations
“…Due to the critical role of POSTN in metastatic processes, it is very likely that this protein may influence some crucial steps in the implantation process and in the early phases of pregnancy development. Recent reports on null POSTN mice, indicate that POSTN, plays an important role in implantation (59,60). We suggest that POSTN might be involved in regulating the cross-talk between embryonic migrating cells and the endometrium modifying the microenvironment of the target site so as to form a "receptive niche" and allowing blastocyst migration, attachment and invasion.…”
Section: Human Embryo Implantation Shares Many Biological Characterismentioning
confidence: 76%
“…Studies on animal models (60,61) showed that POSTN was mainly hyper-expressed in the early secretory stage, the same phase in which there was an increase of integrin α v β 3 and α v β 5 expression too. In this specific phase, POSTN may induce endometrial decidualization, trophoblastic cells migration and invasion through the activation of integrins and the Akt/PKB pathway (60,62). Furthermore, POSTN might activate EMT process via integrins and AKT downstream signaling.…”
Section: Human Embryo Implantation Shares Many Biological Characterismentioning
confidence: 99%
See 2 more Smart Citations
“…It induces endometrial decidualization and promotes migration of trophoblastic cells [30,31]. It is also required for normal embryogenesis [32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%